ANALISIS GAYA BAHASA DALAM NOVEL GANJIL GENAP KARYA ALMIRA BASTARI - Yulia Ika Safitri; Yusron Yusuf (Institute Agama Islam Al-Qolam Malang, 2021)
The focus of this research is to emphasize the analysis of the use of language styles in odd and even odd novels and the most dominant language styles in odd even novels by Almira Bastari. The purpose of this study is to describe the style of language contained in the novel Odd Even by Almira Bastari. The problems that will be explored in this study are: 1) what are the types of language styles in the Odd Genap novel by Almira Bastari, 2) what is the meaning of the style of language contained in the odd even number by Almira Bastari, 3) what are the most dominant language styles in the novel Ganjil Genap by Almira Bastari. The method used in this research is descriptive qualitative research method with the type of library research. The data used in this study are words, sentences, discourse related to the style of language contained in the novel odd even by Almira Bastari. The data source used is 342 pages odd evenly published novel by Gramedia Pustaka Utama, Jakarta. Data collection techniques carried out by library and record techniques the data analysis technique uses the matching method. Based on the analysis of the use of the language style in Almira Bastari's Odd Even Novel, the following conclusions can be drawn: 1) the language style found in Almira Bastari's odd-even novel based on the sentence structure includes repetition. Based on whether or not the meaning directly includes: ellipsis, litotes, hyperbole, and paradox. Based on figures of speech include: simile or equation, and personification. 2) Meaning of Language Style in Almira Bastari's Odd Even Novel a) repetition means denotation, b) ellipsis means denotation, c) litotes means denotation, d) hyperbole means connotation, e) paradox means denotation, f) simile means denotation, g) metaphor means denotation, and h) personification means connotation. 3) The most dominant language style in Almira Bastari's Odd Even novel is ellipsis.